Processing, microstructure, properties, and applications of MoSi2-containing composites: a review - Tapia-López, J.; Pech-Canul, M. I.; García, H. M. (Frontiers in Materials, 2023)
The intermetallic molybdenum disilicide (MoSi2) possesses unique physical, chemical, thermal and mechanical properties that make it compatible with some ceramics (SiC, Al2O3) and metals (Cu, Al) to manufacture composite materials. Its current applications, chiefly limited to heating elements, can be expanded if its properties are judiciously combined with those of other materials like SiC or Al to produce ceramic-and metal-matrix composites with improved mechanical, thermal, functional, or even multifunctional properties. This review presents a perspective on the feasibility of manufacturing ceramic-and metallic-based MoSi2 composite materials. A comprehensive discussion of the pros and cons of current liquid-state and solid-state processing routes for MoSi2 metal-matrix composites and the resulting typical microstructures is presented. Although MoSi2 has been studied for more than five decades, it was not until recently that industrial applications demanding high temperature and corrosion resistance were materialized as a bulk material and a coating. Furthermore, beyond its traditional predilection due to its thermal properties, the most recent applications include it as a contact material in microelectronic components or circuits and optoelectronics. The short-term global growth predicted for the MoSi2 heating elements market is expected to significantly impact possible new applications, considering its potential for reuse and recyclability. A prospective assessment of the application of recycled MoSi2 to composite materials is presented.1.